Sexual Violence on Campus: Student Experiences and Perceptions of Institutional Responses - Nafisah, Lu'lu; Rizqi, Yuditha Nindya Kartika (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Sexual violence in higher education is a global issue with severe impacts on victims' health and academic performance. In Indonesia, its high prevalence is driven by peer norms, patriarchal culture, and inadequate institutional responses. However, critical gaps persist in understanding student perceptions, contributing factors, reporting barriers, and expectations for effective prevention and intervention. This study addresses these gaps by examining perceptions of sexual violence, associated risk factors and impacts, reporting barriers, and preventive expectations among university stakeholders. The research was conducted at Jenderal Soedirman University, employing a qualitative descriptive design that involved 18 informants, including students, counselors, and task force representatives. Data were collected through in-depth interviews and analyzed using content analysis. The findings highlight various forms of violence, including sexual harassment, physical, psychological, and gender-based violence, committed by peers, faculty, or staff. Impacts include psychological trauma and academic disruptions. Barriers to reporting, such as stigma, fear of retaliation, and ineffective mechanisms, were commonly reported. Cultural norms, power imbalances, and insufficient supervision in non-academic activities were found to exacerbate the issue. Informants stressed the need for a shift in cultural attitudes, accessible reporting systems, and victim support services through the implementation of comprehensive prevention and intervention programs.